Visualizing changes in brain-derived neurotrophic factor (BDNF) expression using bioluminescence imaging in living mice - Mamoru Fukuchi (Nature Portfolio, 2017)
Abstract Brain-derived neurotrophic factor (BDNF) plays a fundamental role in expressing various neural functions including memory consolidation. Alterations of BDNF levels in the brain are associated with neurodegenerative and neuropsychiatric disorders. Therefore, it is important to understand how levels of BDNF are controlled. Recently we generated a novel transgenic mouse strain, termed the Bdnf-Luciferase transgenic (Bdnf-Luc Tg) mouse, to monitor changes in Bdnf expression. In the present study, we detected the bioluminescence signal from living Bdnf-Luc Tg mice after intraperitoneal administration of d-luciferin. Despite high levels of Bdnf expression in the brain, it was difficult to detect a signal from the brain region, probably because of its poorly penetrable (short-wavelength) bioluminescence. However, we could detect the changes in the bioluminescence signal in the brain region using a luciferin analogue generating a near-infrared wavelength of bioluminescence. We also found a strong correlation between increases in body weight and bioluminescence signal in the abdominal region of Tg mice fed a high-fat diet. These results show that changes in Bdnf expression can be visualized using living mice, and that the Tg mouse could be a powerful tool for clarification of the role of Bdnf expression in pathophysiological and physiological conditions.